PEDAGOGICAL CONDITIONS OF FORMATION BACHELORS OF TOURISM TO PROFESSIONAL INTERACTION WITH CONSUMERS OF TOURISM SERVICES - Dyshko, Olesya L. (Educological discourse, 2015)
Methodological essence of concept “pedagogical conditions” is disclosed and examined in the article. Complex of pedagogical conditions which promote efficiency of the process of forming readiness of Bachelors of Tourism to professional interaction with consumers of tourism services is defined and characterized.